In-situ microscopy study of grain refinement in the simulated heat-affected zone of high-strength low-alloy steel by TiN particle. (19th May 2017) - Wan, X.; Zhou, B.; Nune, K. C.; Li, Y.; Wu, K.; Li, G.
ABSTRACT: High-strength low-alloy steels subjected to high heat input welding are susceptible to failure due to low toughness caused by grain coarsening. The effect of TiN on grain refinement in the simulated heat-affected zone (HAZ) was investigated. Because of small amount of Ti addition, abundant dispersed nanoscale TiN precipitates were formed. The TiN precipitates tended to be stable at high temperature and effectively retarded the austenite grain growth by refining the grain size during thermal cycle. Furthermore, the TiN also covered on the surface of Al–Ti complex oxide with MnS and caused low interface energy with ferrite. The acicular ferrite grains nucleated on complex inclusion in austenite grains at intermediate temperature and induced the austenite grain transform to the fine-grained mixed microstructure of acicular ferrite and bainite. The crystallographic grain size became small in the simulated HAZ due to the effective pinning effect and acicular ferrite formation.